5 Isu Prioritas Di Dinas Pppa Provinsi Sumatera Selatan Dalam Perspektif Maslahah Mursalah - Dewi, Rusmala; Setianah, Junita Dwi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
This study aims to find out how the perspective of maslahah mursalah regarding the program of 5 priority issues that exist in the PPPA Office of South Sumatra Province and what efforts can be made in terms of dealing with issues that occur in the community. The approach method used is a qualitative method or commonly known as the naturalistic observation method. The results of the study show that the 5 priority issues according to the perspective of maslahah mursalah are in line with the principles of maqashid Syariah and the rules of fiqh. Meanwhile, in handling the case, the efforts that the PPPA Office of South Sumatra Province can do are through advocacy, outreach, and coordination.